New and Renewable Energy: Ensuring the Hydropower Development Policy Meets the Community and the Environmental Participation Based on the Paris Agreement - Rahayu, Devi; Wartiningsih, Wartiningsih; Yogahastama, Riesta (Brawijaya Law Journal, 2022)
Energy demand is rapidly increasing, following population growth and economic trends, including the demand for electrical energy. Indonesia seeks to transition to the use of new and renewable energy to supply its demand for electricity. The national strategic program to construct 65 dams in 2023 is the fundamental foundation for the government’s ability to bring about this massive development. One of the many essential uses of reservoirs is as a source of hydropower energy. However, have been many cases of rejection by local communities that do not consider themselves to have been fairly consulted for or participating in the development process. Another premise of this rejection is founded on environmental issues related to the Paris Agreement. This article focuses on meeting challenges to community and environmental participation based on the Paris Agreement.  New and renewable energy policies incorporate novel regulations pertaining to the government’s authority to work on the new renewable energy projects. Hydropower development projects fall under the government’s efforts to switch to new sources of renewable energy. Insufficient involvement of the local community in development and activities, to the extent that the information and comprehension on where the hydropower dams are expected to be built are exceptionally lacking but are also, due to the impact of the development toward the environment, the main source of refusal from the local community.  Finally in accordance with the Paris Agreement, insufficient attention toward the landscape will likely impair the ability to create future hydropower development projects.